SISTEM INFORMASI PENYEWAAN DAN PEMELIHARAAN ALAT BERAT MENGGUNAKAN METODE LINEAR SEQUENCE PADA CV. SUN PASIFIC DIESEL - Selvia Mago; Abdullah; Sudirman (KHARISMA Tech, 2018)
This research aims to design and build information system rental and maintenance of heavy equipment used to facilitate the presentation of information about the recording, controlling to calculate the cost of heavy equipment on the CV. Sun Pasific Diesel. In this information system using Linear Sequence method according to Pressman (2012) Linear Sequence Model is a classical model that is systematic, sequential in building software and this model is also often referred to as "classic life cycle" or waterfall model.Tahapan in this study is divided into 5 part, that is communication, planning, modeling, construction and deploynment. In the modeling stage includes modeling the system using the use case diagram and data modeling using the entity relationship diagram, then implemented using Visual Basic programming language 2013 and MySQL as the database. Furthermore, testing on this system using Black Box testing method. The results of this research are reports of rental and maintenance of heavy equipment.